KEMAMPUAN METAKOGNISI SEBAGAI SELF REGULATED LEARNING MAHASISWA PPKN FKIP UNIVERSITAS SRIWIJAYA UNTUK MENCAPAI PRESTASI BELAJAR - Ririn Nova Elza; Camellia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the metacognitive ability as self-regulated learning of Pancasila and Citizenship Education (PPKn) students of the Faculty of Teacher Training and Education, Sriwijaya University to achieve academic achievement. This study uses a quantitative approach with a correlational method. This study involved 225 active PPKn students from the classes of 2022, 2023, and 2024. The research sample of 135 respondents was selected using a purposive sampling method. Supporting data consisted of documentation, questionnaires, and interviews. Based on data analysis, a Pearson correlation value of 0.899 was found, indicating that the correlation is included in the category of a very strong relationship. The results of the determination test showed an R² value of 0.808, indicating that 80.8% of learning outcomes are influenced by self-learning, while the remaining 19.2% are influenced by factors outside the study. and the t table value = 1.656. So 15.82 <1.656, which means H0 is rejected and Hα is accepted. Therefore, it can be concluded that there is a positive relationship between metacognitive abilities as part of self-regulated learning and student achievement. This indicates that the higher a student's metacognitive abilities, the higher their academic achievement. Conversely, if metacognitive abilities are low, student achievement tends to be lower.